How spiders determine clutch size - Briceño, R. Daniel (1987)
The relation (in spiders) between food ingestion during the ripening period of the eggs ans size of the brood show that there is reabsorption of eggs and that the average coeficients of variation for aH eggs sizes is closely related to the available sources. These coefficients are higher than those observed for deficient diets (P < 0.05). However at time of laying the average size of the eggs is the same. The spiders probably respond to the presence of great quantities of food by iniciating the development of a large number of eggs. If food consumtion is mantained, a series of additional eggs will be produced. Apparently, the physiological rocesses are linked in a simple manner to the action of a switch. The presence of a certain quantity of food in a given time is the signal that turns on the switch with the incorporation of material into the eggs.